A Review of Application of Genetic Algorithm in Solving Unit Commitment Problem - A. Bukhari, S. B.; Ahmed, A.; Raza, S. A. (The Nucleus, 2020)
Unit commitment (UC) is a non-linear, combinatorial, mixed integer constrained optimization problem. The aim of unit commitment problem (UCP) is obtained the most cost effective on/off schedule for generating units to meet the forecasted load demand and spinning reserve for a specified time horizon. UCP can be seen as a two combined optimization problem, the on/off scheduling problem of generating units and the real power allocation problem. A feasible UC schedule must satisfy various system and unit constraints. Various techniques have been developed to solve generator scheduling problem/ UCP. Natural Evolution based techniques are extensively applied to obtain global optimal solution. Genetic algorithm is one of the evolutionary method. This paper presents a comprehensive review on genetic algorithm based unit commitment problem solution. A survey of all of the research papers up to the year 2013 on this topic is given.